Factors associated with the successful implementation of computerised hospital information systems in South Africa - Hanmer, Lyn Avril (Department of Information Systems, 2014)
A conceptual model of Computerised Hospital Information System (CHIS) use was developed and refined, in order to improve understanding of factors associated with successful CHIS implementation in level 1 and level 2 public sector hospitals in two South African provinces. The study drew on models of information system (IS) success, insights from the HIS evaluation literature and studies of risk factors associated with the implementation of clinical information systems (CISs), in order to synthesise relevant results. A multi method approach was used to investigate the complex study environment. Pilot case studies were conducted in three level 2 hospitals in Province 1, in order to understand the use of CHISs in these environments. The major output of this phase was the initial conceptual model of CHIS use, which identified seven factors associated with successful CHIS implementation. In the second phase of the study, a further case study was conducted at a fourth level 2 hospital in Province 1, and interviews were conducted with three South African CHIS experts. An extended conceptual model of CHIS use was developed on the basis of the data from this phase. In the third and final phase of the study, a survey of CHIS use was conducted in more than thirty level 1 and level 2 hospitals, in two provinces, using one of three CHISs, in order to validate the conceptual model developed in the previous study phase. The results of the case study informed the refinement of the conceptual model to create the revised conceptual model of CHIS use. The conceptual model of CHIS use is a major output of this study. The survey results confirmed that the factors of the conceptual model are associated with CHIS success in level 1 and level 2 hospitals in the study provinces, and supported most of the relationships between the factors in the model. The study provides unique insights into the CHIS implementations in rather poorly resourced environments, thereby contributing to a growing literature on health information system development, implementation and use in developing areas from the perspective of information system success modelling, health information system evaluation, and a developing country context.